Uma análise dos dirigentes dos partidos políticos em São Borja – RS no ano de 2013 - (:unkn) unknown (Universidade Federal do Pampa, 2014)
This paper addresses the issue of party leaders in São Borja, in 2013 . The objective is to identify the characteristics , the profile of who occupies such a position , aspects relating to its operations , as well as the perception that they have about what is a political party . And in that sense, we verify the intricacies of performance thereof within the party fora. Also relying on the perception of such leaders on topics of political conjuncture. The research was carried out through a questionnaire applied to fourteen representatives of party bodies that have representation in the municipal legislature. This instrument is divided into three parts: the first with questions regarding the characteristics of leaders , and the second relates to how the role of leader in a political party and in this case , was asked: what is the reason of membership in the party , since candidate was , as reports on what happens in the country with reference to politics, has participated in the course or activity of party formation , ever read the founding documents of the party , that way voters and members are informed about the topics of discussion the party, if the party usually receives new members , how it occurs and at what time , and the third part , focused on the perception of managers on the status of the party and on the local and national context , and asked the following : what main characteristic of a party leader , should operate as a militant , how you perceive the articulation of his party with , which points considered most problematic in its functioning local community , if there is a training activity within the party , which the requirements necessary to become a party leader and the role of a political party in the community.
Keywords: Partidos políticos; Participação política; São Borja, RS; Political parties; CNPQ::CIENCIAS SOCIAIS APLICADAS